2020
DOI: 10.1186/s12942-020-00210-8
|View full text |Cite
|
Sign up to set email alerts
|

How urban densification shapes walking behaviours in older community dwellers: a cross-sectional analysis of potential pathways of influence

Abstract: Background: Population growth, population ageing, and urbanisation are major global demographic trends that call for an examination of the impact of urban densification on older adults' health-enhancing behaviours, such as walking. No studies have examined the pathways through which urban densification may affect older adults' walking. This information is key to evidence-based, health-oriented urban and transport planning. This study aimed to identify neighbourhood environment characteristics potentially respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 65 publications
(109 reference statements)
4
24
0
Order By: Relevance
“…This could be due to various reasons speci c to the local environment such as area-level socio-economic status or crime rates, factors that were not included in the regression models of land use mix -diversity. Alternatively, the actual level of access to various destinations might have been so high that many respondents could reach destinations with minimal walking In fact, recent studies have observed negative effects of extreme levels of access to destinations on transport-related walking [35,36]. These patterns are more likely to occur in locations with high population and destination densities as in many Latin American cities [6,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to various reasons speci c to the local environment such as area-level socio-economic status or crime rates, factors that were not included in the regression models of land use mix -diversity. Alternatively, the actual level of access to various destinations might have been so high that many respondents could reach destinations with minimal walking In fact, recent studies have observed negative effects of extreme levels of access to destinations on transport-related walking [35,36]. These patterns are more likely to occur in locations with high population and destination densities as in many Latin American cities [6,37].…”
Section: Discussionmentioning
confidence: 99%
“…Only urban areas were included in the study, thus the samples are not nationally representative. The cross-sectional design precludes determination of causality even with careful adjustment for covariates [35,46,47]. The use of self-report measures for both neighborhood environments and PA must be considered in the interpretation of the ndings.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to various reasons specific to the local environment such as area-level socio-economic status or crime rates, factors that were not included in the regression models of land use mix -diversity. Alternatively, the actual level of access to various destinations might have been so high that many respondents could reach destinations with minimal walking In fact, recent studies have observed negative effects of extreme levels of access to destinations on transport-related walking [35,36]. These patterns are more likely to occur in locations with high population and destination densities as in many Latin American cities [6,37].…”
Section: Independent Variablesmentioning
confidence: 99%
“…This could be due to various reasons speci c to the local environment such as area-level socio-economic status or crime rates, factors that were not included in the regression models of land use mix -diversity. Alternatively, the actual level of access to various destinations might have been so high that many respondents could reach destinations with minimal walking In fact, recent studies have observed negative effects of extreme levels of access to destinations on transport-related walking [38,39]. These patterns are more likely to occur in locations with high population and destination densities as in many Latin American cities [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Only urban areas were included in the study, thus the samples are not nationally representative. The cross-sectional design precludes determination of causality even with careful adjustment for covariates [38,46,47]. The use of self-report measures for both neighborhood environments and PA must be considered in the interpretation of the ndings.…”
Section: Discussionmentioning
confidence: 99%